1642 Va. Acts 248, Act 11 - (:unkn) unknown (My University, 1642)
Whereas the rights and interests of the inhabitants are very much infringed by hunting and shooting of diverse men upon their neighbors lands and dividends contrary to the privileges granted to them by their patents, whereby many injuries do daily happen to the great damage of the owners of the land whereon such hunting or shooting is used, It is therefore enacted and confirmed that if any planter or person shall hunt or shoot upon or within the precincts or limits of his neighbor or other divident without leave first obtained for his so doing, and having been warned by the owner of the land to forbear hunting and shooting as aforesaid, he or they so offending shall forfeit for every such offence four hundred pounds of tobacco . . .
Keywords: DISCHARGE; HUNTING REGULATION